Excel as an electronic method for determining thermal diffusivity from experimental data - Camila Rodrigues Carneiro; Mateus Tomaz Neves; Adamu Muhammad Alhaji; Rita de Cássia Superbi de Sousa (The Journal of Engineering and Exact Sciences)
It is undoubted that, with industrial development, the thermophysical characterization of materials and substances, among other reasons, maximizes the performance of equipment and the efficiency of the most diverse unit operations. In these studies, related to thermal diffusivity, a property that is directly related to the heat transfer between materials, are increasingly recurrent. A simple and effective apparatus for estimating thermal diffusivity in an experimental and direct way was developed by Dickerson (1965), and since then it has been widely used in research related to this topic. However, considering that experimentally, a series of data is obtained related, for example, to the dimensions of the equipment, as well as the time values, and efficiently in order to obtain results that make it possible to infer as much information about the object of study as possible. Therefore, with this proposed work, the use of electronic spreadsheets, calculated for Excel data processing, from the experimental Microsoft software obtained by the apparatus. The functionality of the physical spreadsheets was verified through the electronic calculation resolution, in the manual form and in the demonstration of efficiency and agility of the computational method, in addition to the characterization of the potential for several materials or substances.